2002
DOI: 10.1034/j.1600-079x.2002.1o811.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of prostaglandins, nitric oxide, sensory nerves and gastrin in acceleration of ulcer healing by melatonin and its precursor, L‐tryptophan

Abstract: Melatonin, a major hormone of pineal gland, was recently shown to attenuate acute gastric lesions induced by strong irritants because of the scavenging of free radicals but its role in ulcer healing has been little investigated. In this study we compared the effects of intragastric (i.g.) administration of melatonin and its precursor, L-tryptophan, with or without concurrent treatment with luzindole, a selective antagonist of melatonin MT2 receptors, on healing of chronic gastric ulcers induced by serosal appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
57
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 61 publications
(99 reference statements)
8
57
0
Order By: Relevance
“…Brzozowski concluded that the ulcer healing effects of L-arginine are possibly related to NO, gastrin, and polyamines. As expected, repeated administration of NO synthase (NOS) inhibitor 156) resulted in significantly delayed healing of Type 1 acetic acid ulcers in rats. Furthermore, Larginin clearly reversed the effects of NOS inhibitor on ulcer healing.…”
Section: Factors Affecting Ulcer Healingsupporting
confidence: 62%
See 2 more Smart Citations
“…Brzozowski concluded that the ulcer healing effects of L-arginine are possibly related to NO, gastrin, and polyamines. As expected, repeated administration of NO synthase (NOS) inhibitor 156) resulted in significantly delayed healing of Type 1 acetic acid ulcers in rats. Furthermore, Larginin clearly reversed the effects of NOS inhibitor on ulcer healing.…”
Section: Factors Affecting Ulcer Healingsupporting
confidence: 62%
“…Watanabe suggested that the drug exerted its effect by modulating cell kinetics (apoptotic and proliferating cells) and inhibiting neutrophil infiltration (MPO activity). Brzozowski et al 132) found that exogenous melatonin and L-tryptophan significantly accelerated acetic acid ulcer healing in rats, probably via interaction with MT2 receptors. The underlying mechanism appears to involve increases in gastric mucosal blood flow via COX-derived PGs, iNOS-derived NO, and CGRP released from sensory nerves.…”
Section: Miscellaneous Drugs and Endogenous Sub-mentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental studies, melatonin has been shown to be effective in reducing mucosal breakdown in experimental colitis 37 or gastric ulcer. 38 Apart from its radical scavenging activity, melatonin is believed to exert a direct defence on the epithelium and to enhance submucosal blood flow. 11 It was reported that melatonin enhances microcirculation by cyclo-oxygenasederived prostaglandins and nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
“…11 It was reported that melatonin enhances microcirculation by cyclo-oxygenasederived prostaglandins and nitric oxide. 38 Moreover, the hormone is reported to stimulate the synthesis of gastroprotective hormones. It was suggested that gastrin, which exhibits trophic activity and calcitonin gene-related peptide (CGRP), released from sensory nerves, may also contribute to the mucosal protective effects of melatonin.…”
Section: Discussionmentioning
confidence: 99%